Added Value Analysis of Intermediate and Final Cocoa Products: Case Study in a Cocoa Producing Unit in Jember, East Java - Diany Faila Sophia Hartatri; Alvin Rizki Ramadhani; Sholahuddin Akbar; Burhanuddin Fauzi; Hendy Firmanto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Cocoa is one of the important commodities that significantly contribute to Indonesian economy. Moreover, millions farmers depend on this commodityas their main source of income. However, the low quality of dried cocoa beans produced by Indonesian smallholder cocoa farmers has led the low farm-gateprice. Therefore, efforts for increasing the cocoa income are required. Hilirisasi (down streeming) program has been implemented by the Government of Indonesia (GoI), including in cocoa commodity in order to increase the added value ofcocoa. There are various downstream products, including intermediate and final products that can be produced. The intermediate products include paste/liquor,cocoa butter, and cocoa powder, meanwhile the final products, such as 3 in 1 cocoa powder, milk chocolate bars and dark chocolate bars. Research on addedvalue of intermediate and final cocoa products specially in small size producing units is still limited, whereas this research is required to support the nationaleconomy and smallholder cocoa farmers. Therefore, this research aims to understand the added value of producing intermediate and final cocoa products at asmall sized enterprises of cocoa processing unit based in Jember, East Java. This research was conducted in March to June 2020 by conducting observation, documentation and interview for understanding the production activities of intermediateproducts (cocoa paste/liquor, cocoa butter and cocoa powder) and final products (3 in 1 milk powder, milk chocolate bar and dark chocolate bar). The researchresults show that producing intermediate and final products resulted in medium to high added value and profitable for the producing unit. Producing cocoa paste/liquor generated the highest profit among the intermediate cocoa products, meanwhile on final cocoa products, processing 3 in 1 cocoa powder provided thehighest profit. In order to increase the national and community economy, the support of GoI to small and medium enterprise (SMEs) or farmer groups for processing the downstream cocoa products is required. Cocoa is one of the important commodities that significantly contributeto Indonesian economy. Moreover, millions farmers depend on this commodity as their main source of income. However, the low quality of dried cocoa beansproduced by Indonesian smallholder cocoa farmers has led the low farm-gate price. Therefore, efforts for increasing the cocoa income are required. Hilirisasi(down streeming) program has been implemented by the Government of Indonesia (GoI), including in cocoa commodity in order to increase the added value ofcocoa. There are various downstream products, including intermediate and final products that can be produced. The intermediate products include paste/liquor,cocoa butter, and cocoa powder, meanwhile the final products, such as 3 in 1 cocoa powder, milk chocolate bars and dark chocolate bars. Research on addedvalue of intermediate and final cocoa products specially in small size producing units is still limited, whereas this research is required to support the nationaleconomy and smallholder cocoa farmers. Therefore, this research aims to understand the added value of producing intermediate and final cocoa products at asmall sized enterprises of cocoa processing unit based in Jember, East Java. This research was conducted in March to June 2020 by conducting observation, documentation and interview for understanding the production activities of intermediateproducts (cocoa paste/liquor, cocoa butter and cocoa powder) and final products (3 in 1 milk powder, milk chocolate bar and dark chocolate bar). The researchresults show that producing intermediate and final products resulted in medium to high added value and profitable for the producing unit. Producing cocoa paste/liquor generated the highest profit among the intermediate cocoa products, meanwhile on final cocoa products, processing 3 in 1 cocoa powder provided thehighest profit. In order to increase the national and community economy, the support of GoI to small and medium enterprise (SMEs) or farmer groups for processing the downstream cocoa products is required.